2021
DOI: 10.1111/fcp.12737
|View full text |Cite
|
Sign up to set email alerts
|

Vortioxetine as an analgesic in preclinical inflammatory pain models: Mechanism of action

Abstract: Vortioxetine is a novel atypical antidepressant with multimodal activity that has recently demonstrated efficacy against neuropathic pain. There is no published data about its analgesic properties in models characterized by peripheral inflammation and consequent pain pathway sensitization, nor data on its mechanism of antinociceptive action. This study aimed to investigate vortioxetine's antinociceptive/antihyperalgesic effects in trigeminal, visceral, and somatic inflammatory pain models, and provide evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
(96 reference statements)
1
7
0
Order By: Relevance
“…These findings pointed out that muscarinic receptors, as well as the α 2 -, β 2 - and D 2 /D 3 -catecholaminergic receptors, participate in the aforementioned effect of vortioxetine. The results of a previous study by Todorović and co-workers suggesting that the analgesic activity of vortioxetine against trigeminal, visceral and somatic inflammatory pain is at least partially mediated by the α 2 /β 1 -adrenergic and muscarinic cholinergic receptors support the findings of our mechanistic studies [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings pointed out that muscarinic receptors, as well as the α 2 -, β 2 - and D 2 /D 3 -catecholaminergic receptors, participate in the aforementioned effect of vortioxetine. The results of a previous study by Todorović and co-workers suggesting that the analgesic activity of vortioxetine against trigeminal, visceral and somatic inflammatory pain is at least partially mediated by the α 2 /β 1 -adrenergic and muscarinic cholinergic receptors support the findings of our mechanistic studies [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, based on previous reports presenting the therapeutic potential of vortioxetine for acute [ 12 , 13 ], inflammatory [ 11 ] and neuropathic pain [ 7 , 14 ], the potential efficacy of this drug against diabetes-induced hyperalgesia and allodynia responses was investigated in rats. Further mechanistic studies were conducted in order to elucidate the promising contributions of the catecholaminergic and cholinergic systems to the antihyperalgesic and antiallodynic activities of vortioxetine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researches proved the antinociceptive effects of carrageenan-induced paw inflammation in mice [42], but others noted the lack of influence of this antidepressant in the inflammatory neuropathic pain [39]. The antinociceptive properties of VRT in neuropathic pain may be due to the antagonism of 5-HT3 receptors and the modulation of the 5-HT7 receptors, as well as due to its anti-inflammatory activity with favorable effects on the decreasing in neuro-inflammation associated with these types of chronic hyperalgesia [39,43].…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that ketamine-blockade of NMDA receptors exerts its analgesic effects via modulation of NO synthesis. We have hence used inhibitors of NOS, including L-Nitro-Arginine Methyl Ester (L-NAME) as the non-specific NOS inhibitor, aminoguanidine (AG) as inducible NOS (iNOS) inhibitor, and 7-Nitroinidazole (7-Ni) as the selective inhibitor of neuronal NOS (nNOS) in the current study to determine the role of nitric oxide pathway associated with NMDA blockade by ketamine, using routine pain assessment behavioral tests as well as western blot [15]; the latter owing to the fact that L-NAME [16] and aminoguanidine [17] cause reduction in the NOS mRNA as well. Furthermore, we have tested the effect of chronic ketamine administration, since it is previously demonstrated that some effects may appear in chronic doses, which were acutely inactive [18].…”
mentioning
confidence: 99%